Bisnis Online Menurut Etika Bisnis Islam dengan Sistem Reseller di Desa Bantarjati Kecamatan Klapanunggal - Yunus, Acep; Asri, Kholifatul Husna (ALIF: Sharia Economics Journal, 2023)
In this era, sellers can take advantage of many technological developments, such as online sales transactions. Business actors need to be reviewed and analyzed in terms of the practice of buying and selling online with the reseller system and the application of Islamic business ethics in buying and selling online with the reseller system in Indonesia has been implemented properly and correctly. In this study, data was collected through a questionnaire which was distributed to 10 people where the respondents had been involved in the online reseller sales system. The results of the responses to this questionnaire will be collected for observation and analysis in more detail and depth. The results of this study indicate that, of the 10 informants buying and selling online with a reseller system, at least there are still those who have not implemented Islamic business ethics. This can be seen from the explanation of shop operating hours and delivery of goods, responsibility for the products sold and complaints from consumers, and being honest in selling does not display images that are not from the product itself. Business actors must understand, understand and apply Islamic business ethics in order to create a sense of justice and protect consumer rights in buying and selling transactions online. Islamic business ethics includes four aspects, honest and trustworthy, disciplined, responsible and grateful.